2020
DOI: 10.3390/app10217753
|View full text |Cite
|
Sign up to set email alerts
|

Stress–Strain Model for Freezing Silty Clay under Frost Heave Based on Modified Takashi’s Equation

Abstract: In analyzing frost heave, researchers often simplify the compressive modulus of freezing soil by considering it as a constant or only as a function of temperature. However, it is a critical parameter characterizing the stress–strain behavior of soil and a variable that is influenced by many other parameters. Hence, herein several one-dimensional freezing experiments are conducted on silty clay in an open system subjected to multistage freezing by considering the compressive modulus as a variable. First, freezi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…e uniaxial compressive strength of frozen red clay increases with the decrease of temperature. When the temperature field in the soil changes, water migration will occur [29]. e strength growth rate is different at each stage, the strength increases most obviously at −2 °C∼−10 °C, and the effect of temperature on strength decreases between −10 °C∼−15 °C.…”
Section: The Relationship Between Uniaxial Strength and Temperaturementioning
confidence: 99%
“…e uniaxial compressive strength of frozen red clay increases with the decrease of temperature. When the temperature field in the soil changes, water migration will occur [29]. e strength growth rate is different at each stage, the strength increases most obviously at −2 °C∼−10 °C, and the effect of temperature on strength decreases between −10 °C∼−15 °C.…”
Section: The Relationship Between Uniaxial Strength and Temperaturementioning
confidence: 99%
“…Wang et al conducted a lot of freezing tests of unsaturated soil, considering the influence of fine content and degree of saturation [9]. Geng et al examined coarse aggregate differently and discovered that the coagulation potential decreased with the gradual increase in porosity of coarse aggregate and confirmed that the coagulation potential should be considered because of fine-grain content [10]. Tang et al proposed that the range of fine soil and freezing conditions have the greatest influence on the frost heave sensitivity of water-saturated sand and gravel during freezing [11].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the overall promotion of transportation, the development of highways and railways has rapidly developed, and the number of urban deep foundation pit projects has correspondingly increased. In China, frozen soil is widely distributed [1,2]. In seasonally frozen soil areas, the foundation pit active layer of the soil experiences repeated freeze thaw action, considerably affecting the stability of related projects such as building sites and subway stations.…”
Section: Introductionmentioning
confidence: 99%